Familial cases of a submicroscopic Xp22.2 deletion: genotype-phenotype correlation in microphthalmia with linear skin defects syndrome - Vergult, Sarah (Molecular Vision, 2013)
PURPOSE: Microphthalmia with linear skin defects syndrome (MLS or MIDAS, OMIM #309801) is a rare X-linked male-lethal disorder characterized by microphthalmia or other ocular anomalies and skin lesions limited to the face and neck. However, inter- and intrafamilial variability is high. Here we report a familial case of MLS. METHODS: A mother and daughter with MLS underwent a complete ophthalmological examination, and extensive imaging, including anterior segment pictures, corneal topography and keratometry, autofluorescence, infrared reflectance and red free images, as well as spectral-domain optical coherence tomography. The mother also underwent full-field flash electroretinography. In addition, high-resolution array comparative genomic hybridization analysis was performed in both as well as in the maternal grandparents of the proband. RESULTS: Microphthalmia and retinal abnormalities were noted in the proband and the mother, whereas only the mother presented with scars of the typical neonatal linear skin defects. Array comparative genomic hybridization analysis revealed a 185–220 kb deletion on chromosome band Xp22.2 including the entire HCCS gene. CONCLUSIONS: The identification of a deletion including HCCS led to the diagnosis of MLS in these patients. Retinal abnormalities can be part of the ocular manifestations of MLS.